Inpatient Opioid Use After Vaginal Delivery. Issue 3 (September 2019) - Badreldin, N.; Grobman, W.A.; Yee, L.M.
Abstract : ( Am J Obstet Gynecol . 2018;219:608.e1–608) Inpatient opioid use may serve as a first opioid exposure for many patients undergoing labor and delivery, as well as result in subsequent opioid abuse or dependence. However, data regarding this issue in this patient population are limited; current literature largely focuses on outpatient opioid prescription and treatment for the management of postdelivery pain. Therefore, this study evaluated opioid use in women during postpartum hospitalization and identified both maternal and prescribing provider characteristics associated with opioid prescription and use.